Fuzzy boundaries between hyponymy and meronymy - Pišković, Tatjana (Poznańskie Studia Slawistyczne, 2025)
Lexical hierarchies are based on the relation between a superordinate lexeme that has a broader, more general meaning and its subordinate lexemes that have narrower, more specific meanings. In the lexical hierarchy, a relation of domination, which is vertical and established between members located at different levels of the hierarchy, is recognized, as well as a relation of differentiation, which is horizontal and established between members located at the same level of the hierarchy. Lexemes from lower levels represent a type or a part of what their superordinate lexemes denote, so two basic types of lexical hierarchies are distinguished: hyponymy is based on the relation between a genus and a species, while meronymy is based on the relation between a whole and a part. In this article, we will focus on lexical hierarchies for which it is difficult to determine whether they illustrate hyponymic or meronymic relations, revealing the hybrid relation that arises from their blending.